2019
DOI: 10.1039/c9ra04987h
|View full text |Cite
|
Sign up to set email alerts
|

Normal force of lithium-based magnetorheological grease under quasi-static shear with large deformation

Abstract: An experimental study was conducted to explore the normal force of lithium-based magnetorheological (MR) grease under quasi-static shear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Besides, larger normal stress will be achieved at larger magnetic field strength. Transformation of normal stress from stage 1 to stage 2 and then to stage 3 could be explained with a microstructure theory (Lopez-Lopez et al, 2010;Wang et al, 2019), as shown in Figure 8. The randomly dispersed magnetic particles (Figure 8A) will aggregate to vertical chain-like structures (Figure 8B) within milliseconds as soon as a magnetic field is applied, resulting in the magnetic interaction and attractive force between the magnetic particles.…”
Section: Influence Of Magnetic Field On the Normal Stress Behaviormentioning
confidence: 98%
See 2 more Smart Citations
“…Besides, larger normal stress will be achieved at larger magnetic field strength. Transformation of normal stress from stage 1 to stage 2 and then to stage 3 could be explained with a microstructure theory (Lopez-Lopez et al, 2010;Wang et al, 2019), as shown in Figure 8. The randomly dispersed magnetic particles (Figure 8A) will aggregate to vertical chain-like structures (Figure 8B) within milliseconds as soon as a magnetic field is applied, resulting in the magnetic interaction and attractive force between the magnetic particles.…”
Section: Influence Of Magnetic Field On the Normal Stress Behaviormentioning
confidence: 98%
“…This phenomenon indirectly implies that the effect of shear deformation on normal stress behavior is much weaker than that of the magnetic field. When a magnetic field is applied, normal stress of MRG firstly appears an abrupt increase (stage 1), then decreases rapidly with the increase of shear strain (stage 2), and finally reaches a plateau after the shear strain exceeds a critical value (stage 3) (Wang et al, 2019). Besides, larger normal stress will be achieved at larger magnetic field strength.…”
Section: Influence Of Magnetic Field On the Normal Stress Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…Among all kinds of transportation modes, road transportation and civil aviation transportation are well-known transportation modes with low energy efficiency; Thirdly, with the rapid economic development of Zhongshan, Jiangmen and other places, and the continuous improvement of port facilities, the number of water transport ships will further increase. Affected by the above three factors, the number of ships will continue to increase in the future, and the risk of pier collision will gradually increase [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As known, the exterior loading applied to MR materials are basically categorized into three kinds: static loading, dynamic loading and quasi-static loading. [23][24][25] However, the current experiments on the rheological properties of MRG are almost conducted under the static and dynamic shear. To the best of our knowledge, the investigation on the rheological properties of MRG under quasistatic shear has never been reported.…”
Section: Introductionmentioning
confidence: 99%